2023
DOI: 10.21608/ajas.2023.172232.1197
|View full text |Cite
|
Sign up to set email alerts
|

Fortification of ice milk with purslane (Portulaca oleracea) bioactive compounds

Abstract: The purslane ice milk was made with the addition of purslane extract at levels of 0.0, 0.1, 0.2, 0.3, and 0.4% for control, T1, T2, T3 and T4, respectively. Integrating purslane extract led to a significant decrease in density (from 0.725 to 0.652 g/cm3) as well as weight per gallon (from 6.05 to 5.44 lb.) in the resultant ice milk. On the other hand, the overrun percentage was increased from 41.20 to 58.90%. T4, which contained the greatest purslane extract (0.4%), gained the highest values of milting resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…Additionally, regarding the moisture changes caused by PuE concentrations, a substantial increase in fat content was detected between untreated and treated yogurts after four weeks of cold preservation (p < 0.05) [65]. Our results agree with Osman et al [71], who included purslane extract at four levels 0.0, 0.1, 0.2, 0.3, and 0.4% in ice cream and found a decrease in pH and total carbohydrates. Additionally, Salahi et al [30] found that supplementation of yogurt with purslane leaf extract and preservation for 21 days at 4 • C significantly affected the physicochemical and sensory properties (p < 0.05).…”
Section: Physiochemical Parameterssupporting
confidence: 91%
“…Additionally, regarding the moisture changes caused by PuE concentrations, a substantial increase in fat content was detected between untreated and treated yogurts after four weeks of cold preservation (p < 0.05) [65]. Our results agree with Osman et al [71], who included purslane extract at four levels 0.0, 0.1, 0.2, 0.3, and 0.4% in ice cream and found a decrease in pH and total carbohydrates. Additionally, Salahi et al [30] found that supplementation of yogurt with purslane leaf extract and preservation for 21 days at 4 • C significantly affected the physicochemical and sensory properties (p < 0.05).…”
Section: Physiochemical Parameterssupporting
confidence: 91%
“…The total phenolic and total flavonoid contents also increased in the line of purslane extract concentration. The authors indicated that purslane can be used as a functional food ingredient due to its antioxidant activity [163].…”
Section: Protein-polyphenol Productsmentioning
confidence: 99%